Edukasi Sosialisasi Digital Talent Management pada UMKM Emping Jagung di Desa Banyu Urip - Melita, Dina; Sabilillah, Rizky; Noviardy, Andrian; Elpanso, Efan; Heriyanto, Heriyanto (Pakis Journal Institute, 2026)
The community service titled “Education and Socialization of Digital Talent Management for Corn Chips MSMEs in Banyu Urip Village” was carried out as part of the Thematic Community Service Program (KKNT) at Universitas Bina Darma. This activity was motivated by the limited digital literacy and managerial capacity of MSME actors, which affects the efficiency and competitiveness of small-scale businesses. The aim of this service was to introduce and implement the concept of Digital Talent Management (DTM) as a strategy for improving human resource management in the industrial sector. The method used was a qualitative approach through observation, interviews, and training to help MSMEs utilize simple digital tools such as Microsoft Excel and social media for data management, marketing, and recruitment. The results showed that business actors began to understand the importance of structured and technology-based management. The implementation of DTM encouraged local MSMEs to adapt to digital transformation, thereby enhancing their productivity and business sustainability.